Rancang Bangun Sistem Otomatisasi Pembuatan Telur Asin Berbasis Mikrokontroller - Hadiwiyatno Hadiwiyatno; Rachmad Saptono; Moh Rizqy Al Bana (Politeknik Negeri Malang, 2022)
Duck eggs are an animal food that can be consumed. In community life, generally there are two ways of salting, namely the first with water, salt, and bricks. The process of mixing water and salt still uses the manual method, namely by hand. Salt is a major factor in the salting process of eggs which functions as a preservative to prevent spoilage of eggs, thereby increasing their shelf life. In order to become salted eggs in general, that is by preservation. The method used is experimental, the purpose of experimental research is to create or develop an existing research.The test results on this tool are to produce specification data or to get certainty whether a tool is functioning properly or not. So that if there is damage to the tool or equipment it cannot run properly, it can be analyzed precisely and easily, and we can conclude that the difference in the results obtained from one day to the next